2021
DOI: 10.3389/fonc.2021.605810
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Risk Factor Model Based on Glycolysis-Associated Genes for Predicting the Prognosis of Patients With Prostate Cancer

Abstract: BackgroundProstate cancer (PCa) is one of the most prevalent cancers among males, and its mortality rate is increasing due to biochemical recurrence (BCR). Glycolysis has been proven to play an important regulatory role in tumorigenesis. Although several key regulators or predictors involved in PCa progression have been found, the relationship between glycolysis and PCa is unclear; we aimed to develop a novel glycolysis-associated multifactor prediction model for better predicting the prognosis of PCa.MethodsD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Ankyrin repeat and zinc finger peptidyl tRNA hydrolase 1 (ANKZF1) is essential for the oxidative stress and the maintenance of mitochondrial integrity ( 28 ). Some bioinformatics analyses have proved that ANKZF1 based genes signature can predict the prognosis of patients with colon cancer, renal cell carcinoma, and prostate cancer ( 14 , 29 33 ). ETS proto-oncogene 1, transcription factor (ETS1) is a transcription factor belong to the ETS domain family.…”
Section: Discussionmentioning
confidence: 99%
“…Ankyrin repeat and zinc finger peptidyl tRNA hydrolase 1 (ANKZF1) is essential for the oxidative stress and the maintenance of mitochondrial integrity ( 28 ). Some bioinformatics analyses have proved that ANKZF1 based genes signature can predict the prognosis of patients with colon cancer, renal cell carcinoma, and prostate cancer ( 14 , 29 33 ). ETS proto-oncogene 1, transcription factor (ETS1) is a transcription factor belong to the ETS domain family.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, abundant studies indicate that HMMR plays multiple functional roles in regulating proliferation and metastasis 11 , maintenance of stemness 12 and chemotherapy resistance 13 in various tumours, such as lung cancer 14 , liver cancer 15 , bladder cancer 11 , gastric cancer 16 . Additionally, our previous study found that HMMR was elevated in PCa tumours tissues and associated with poor prognosis 17 . Although the oncogenicity of HMMR in PCa is preliminary disclosed, the precise roles and mechanisms remain largely poor understood, which deserves further explored.…”
Section: Introductionmentioning
confidence: 94%
“…Our previous study characterised HMMR as a crucial tumour driver in PCa 17 . Based on this, we carried out a series of experiments to explore the roles and mechanisms of HMMR.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the metabolic mechanisms that regulate metastasis would, therefore, provide valuable information about precision medicine strategies to prevent or treat metastases. Glycolysis does play an important role in tumorigenesis because separately knocking down several glycolysis‐regulating genes (HMMR, KIF20A, PGM2L1, and ANKZF1) resulted in less glucose consumption, less lactic acid production, and reduced cell migration and invasion of prostate cancer cells 40 . A risk score based on glycolysis‐related genes may serve as an accurate prognostic marker for prostate cancer patients with biochemical recurrence.…”
Section: Cancer Metabolism In Metastatic Cellsmentioning
confidence: 99%
“…Glycolysis does play an important role in tumorigenesis because separately knocking down several glycolysis-regulating genes (HMMR, KIF20A, PGM2L1, and ANKZF1) resulted in less glucose consumption, less lactic acid production, and reduced cell migration and invasion of prostate cancer cells. 40 A risk score based on glycolysis-related genes may serve as an accurate prognostic marker for prostate cancer patients with biochemical recurrence. For these reasons, most research in recent years has focused on glycolytic pathways driving tumor growth (Warburg effect).…”
Section: Cancer Metabolism In Metastatic Cellsmentioning
confidence: 99%